A damage-coupled viscoplastic model for compressed asphalt concrete. Issue 6 (January 2021) - Zeng, Guowei; Liu, Lei; Bai, Fan
Abstract: The damage theory is employed to investigate the mechanical strength deterioration caused by micro defects. Introducing the effective stress, this paper presents a damage-coupled viscoplastic model by applying the Schwartz model with an elastic component. The model is calibrated and validated by asphalt concrete creep test under various stresses. With the help of recursive numerical method, the model parameters include viscoplastic and damage functions for different stresses are determined. The result shows the model not only characterize the three stage creep deformation behaviour at a range of stress, but also can predict the damage evolution during the increased creep strain.